Особливості встановлення ознак об’єктивної сторони порушення правил безпеки дорожнього руху або експлуатації транспорту особами, які керують транспортними засобами - Бесчастна, В. В.; Beschastna, V. V. (Право.uа. – 2019. – № 1. – С. 103-108, 2019)
У статті досліджено особливості встановлення ознак об’єктивної сторони порушення правил безпеки дорожнього руху або експлуатації транспорту особами, які керують транспортними засобами. Обов’язковими ознаками об’єктивної сторони злочину, передбаченого ст. 286 КК, визнано діяння у вигляді порушення правил безпеки дорожнього руху або експлуатації транспорту, суспільно небезпечні наслідки, зазначені у частинах 1-3 ст. 286 КК, необхідний причинний зв’язок між ними, знаряддя й обстановку вчинення злочину.

The article examines peculiarities of establishing elements of objective side of violation of rules related to traffic or driving safety by drivers, which pose difficulties for law-enforcement agent. They are connected with specificity of objective elements of this crime, which specifically connected with the use of mechanic vehicles and their use in traffic conditions. Peculiarity of disposition of the Art. 286 of the Criminal Code is that law-enforcement agent should address other normative-legal acts to ascertain the content of the violated rule related to traffic or driving safety. An action as a part of objective side of violation of rules related to traffic or driving safety by drivers can be presented by: 1) violation of rules related to traffic; 2) violation of rules related to driving safety. The article examines legal regulation of these rules. The article substantiates that besides establishing socially dangerous consequences, defined in the Art. 286 of the Criminal Code, establishing necessary causal connection is very complicated. Special difficulties in establishing necessary causal connection are posed, when several road users violate the rules related to traffic or driving safety at the same time. In such cases the courts must ascertains the character of violations committed by each driver, and also if violation committed by one driver was not caused by violation committed by the other and ability of the first driver to avoid an accident and its consequences. It should be noted that under certain conditions criminal liability is excluded if proven that the driver violated traffic rules under emergency situation produced by the other driver. Legal practice and conclusions of the Supreme Court of Ukraine related to such issues are examined. The article concludes that compulsory elements of objective side of the crime, provided in the Art. 286 of the Criminal Code, are the following: an act of violation of rules related to traffic or driving safety, socially dangerous consequences, provided in the parts 1-3 in the Art. 286 of the Criminal Code, necessary causal connection, instrument presented by a mechanic vehicle and situation of crime presented by committing a violation under traffic rules regulation. It emphasized that only those socially dangerous consequences can be incriminated to a driver which have necessary causal connection with the violation of rules related to traffic or driving safety.

В статье исследованы особенности установления признаков объективной стороны нарушение правил безопасности дорожного движения или эксплуатации транспорта лицами, которые управляют транспортными средствами. Обязательными признаками объективной стороны преступления, предусмотренного ст. 286 УК, признаны деяние в виде нарушения правил безопасности дорожного движения или эксплуатации транспорта, общественно опасные последствия, предусмотренные в частях 1-3 ст. 286 УК, необходимая причинная связь между ними, орудие и обстановка совершения преступления.
Peculiarities of establishing elements of objective side of violation of rules related to traffic or driving safety by drivers
Бесчастна, В. В. Особливості встановлення ознак об’єктивної сторони порушення правил безпеки дорожнього руху або експлуатації транспорту особами, які керують транспортними засобами / В. В. Бесчастна // Право.uа. – 2019. – № 1. – С. 103-108.
Keywords: Кримінальне право. Criminal Law. Уголовное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; порушення правил безпеки дорожнього руху або експлуатації транспорту особами, які керують транспортними засобами; об’єктивна сторона злочину; ознаки злочину; безпека дорожнього руху; транспортні засоби; violation of rules related to traffic or driving safety by drivers; objective side of the crime; elements of the crime; нарушение правил безопасности дорожного движения или эксплуатации транспорта лицами, которые управляют транспортными средствами; объективная сторона преступления; признаки преступления